Epidemiological profile and pain degree in women who inserted intrauterine device (Research, Society and Development, 2021)
The intrauterine device (IUD) is a long-acting reversible contraceptive (LARC) option and has a low cost to the health system. It is an excellent cost-effective strategy for contraception. This study aimed to characterize the epidemiological profile of women who had an IUD inserted, in addition to evaluating the degree of pain during insertion, correlating it with age and obstetric variables. This is a retrospective study with women who inserted an IUD in a reference service in Sergipe between November 2018 and February 2021. Information such as age, number of pregnancies, deliveries and abortions before IUD insertion, pathology or reason for IUD indication, pain scale, hysterometry and wire size after insertion was analyzed. The study included 346 women who inserted copper IUDs and 47 who inserted hormonal IUDs. The mean age of patients was 27.1 years and 33.7 years, mean pain was 4.6 and 5.5 and mean hysterometry was 8.29 and 8.55, respectively. It was noticed that more than 60% of women had at least one pregnancy prior to insertion of the device, in both cases. There was no correlation between pain level and age and parity. Most women who inserted IUDs were in the post-adolescent phase. In addition, most had already had at least one previous pregnancy and experienced moderate pain during IUD insertion.